2012
DOI: 10.1159/000345533
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Chronic Smoking on the Pupil and Photostress Recovery Time

Abstract: Purpose: To determine the effect of chronic smoking on the pupil and photostress recovery time. Methods: Macular adaptation to photostress condition, and mesopic and photopic pupillary responses were measured using automated perimetry (Humprey®), and an OPD device (Nidek), respectively. Forty heavy smokers (smoking ≥1 box/day for the past 5 years at least), and 40 age- and sex-matched nonsmokers were enrolled. All the subjects had full vision and no ocular problems. Results: The baseline foveal threshold value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The results of this study showed a significant decrease in PD at 5 mins after ST use compared to the measurements taken before ST use (4.23±0.51mm vs. 4.52±0.60mm).This was consistent with the findings of Erdem et al (8), who suggested that the iris sphincter muscle was activated more by the parasympathetic system than by the sympathetic system. It has also been suggested that as a result of nicotine binding to nicotinic cholinergic receptors, the induced cholinergic activity causes myosis, resulting in parasympathetic activity in the iris sphincter muscle (12,14). It was similarly thought in the current study that the parasympathetic effect of the nicotinic receptors in the iris sphincter muscle was more predominant than the sympathetic effect in the early stage.In a study conducted by Bardak et al (12), it was reported that no effect of cigarette smoking was determined on PD in the acute stage.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The results of this study showed a significant decrease in PD at 5 mins after ST use compared to the measurements taken before ST use (4.23±0.51mm vs. 4.52±0.60mm).This was consistent with the findings of Erdem et al (8), who suggested that the iris sphincter muscle was activated more by the parasympathetic system than by the sympathetic system. It has also been suggested that as a result of nicotine binding to nicotinic cholinergic receptors, the induced cholinergic activity causes myosis, resulting in parasympathetic activity in the iris sphincter muscle (12,14). It was similarly thought in the current study that the parasympathetic effect of the nicotinic receptors in the iris sphincter muscle was more predominant than the sympathetic effect in the early stage.In a study conducted by Bardak et al (12), it was reported that no effect of cigarette smoking was determined on PD in the acute stage.…”
Section: Discussionsupporting
confidence: 60%
“…Also, various ocular disorders such as thyroid ophthalmopathy, retinal vascular occlusion, and glaucoma, are associated with nicotine (13). Although few, there are also studies in literature related to the effect of nicotine and cigarette smokingon the corneal endothelium, pupil diameter and the lens (8,(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Partic ularly, stimulants and sedatives act to broadly increase and decrease pupil size respectively [82] but the phys iological mechanism matters: drugs acting on the parasympathetic and sympathetic nervous systems differ entially innervate the iris sphincter and pupillary dilator muscles respectively[41] 6 . Smoking gives an acute increase in pupil size by suppressing parasympathetic activity [61], but not on longer timescales [86]. Over vari able timescales, pupil dilation changes with environmental illumination levels, such as those in the workplace, at home, and places in between, perhaps on a diurnal timescale.…”
Section: Changes In the Eye Itselfmentioning
confidence: 99%
“…The photopic pupil diameters were not significantly different between smokers and non-smokers. Sobaci et al 12 proposed that chronic smoking might dilate the pupil. The authors reported larger photopic pupil sizes in smokers and they associated this finding as a result of nicotineinduced autonomous neuropathy.…”
Section: Discussionmentioning
confidence: 99%